Phytochemicals Confer Neuroprotection in Models of Contaminant-induced Neurodevelopmental Disorders - Bessetti, Riley N. (East Carolina University)
Phytochemicals that target antioxidant and anti-inflammatory pathways have gained attention as promising interventions for mitigating oxidative stress and neuroinflammation in neurodevelopmental and neurodegenerative disorders. Many neurodevelopmental disorders, such as autism spectrum disorder (ASD), are linked to oxidative stress-driven disruptions in neural development. Among the many contributing factors, fetal exposure to environmental insults including maternal infection, pollution, and pharmaceuticals increase oxidative stress and the likelihood of ASD development. The response to cellular oxidative stress is regulated in part by the transcription factor Nuclear Factor Erythroid 2-related Factor 2 (NRF2), which promotes phase II enzyme and antioxidant gene expression. The work described in this dissertation investigates the neuroprotective potential of two phytochemicals, sulforaphane and cannabidiol (CBD), focusing on their ability to activate the NRF2 pathway. Using human induced pluripotent stem cell (iPSC) technology, we modeled the susceptibility of early brain development to the toxicant valproic acid (VPA) in vitro with parallel assessment in primary mouse cultures. Sulforaphane robustly activates NRF2-mediated antioxidant responses, mitigating VPA-induced oxidative stress and synaptic alterations. In contrast, CBD recruits NRF2 to the nucleus without increasing transcription of antioxidant genes, but may promote neuroprotection through the suppression of neuroinflammatory pathways. Our continuing work, influenced by the growing recognition of the role of neuroinflammation in neurodevelopmental disorders, explores how phytochemicals modulate inflammatory responses. Ultimately, these findings contribute to our understanding of how NRF2 activators and the regulation of oxidative stress and inflammation can be harnessed as potential preventative strategies to combat environmental exposures that increase the risk of neurodevelopmental disorders.
Keywords: Biology, Neuroscience